Evaluation of accelerated biodegradation of oil-SPM aggregates (OSAs). (March 2020) - Leoncio, Lua; de Almeida, Marcos; Silva, Marcio; Oliveira, Olívia M.C.; Moreira, Ícaro T.A.; Lima, Danúsia Ferreira
Abstract: The studies of the formation of oil-Suspended Particulate Matter (SPM) aggregates (OSAs) have advanced significantly in the scientific community, however there is a need to accelerate oil biodegradation that was dispersed by the formation of OSAs. The present research presents a pioneering character regarding the addition of nutrients as biostimulus for autochthonous hydrocarboclastic bacteria in the biodegradation of Total Petroleum Hydrocarbons (TPH) dispersed by the formation of OSAs. Water aliquots were taken over 60 days from eight bioreactors to perform ionic species analysis, pH, salinity and temperature monitoring, liquid/liquid extraction, serial dilution methodology and filter membrane. TPH quantification was performed on the gas chromatograph with a flame ionisation detector (GC-FID). The addition of nutrients contributed positively to the rate and extent of biodegradation of TPH in association with field-collected SPM. The best result found was with the lowest nutrient concentration (Bio 1) with an average of 98.65% of TPH reduction. Graphical abstract: Unlabelled Image Highlights: Dilution in the concentration of HTPs due to biostimulation The lowest concentration of nutrients was as effective as the highest concentration. Increase in the number of OSAs formed Extension of the lag phase for bioreactors without biostimulation Interspecific competition